Economic Analysis of Energy Storage Preventing Energy Outages in Distribution Grid in Turkey - Tercan, Said Mirza; Gokalp, Erdin; Kekezoglu, Bedri (IEEE, 2018)
Energy outage (EO) is one of major energy quality problems. Turkish Energy Market Regulatory Authority (EPDK) forces distribution companies (DCs) to limit outage time and frequency in certain values. Otherwise EPDK require DCs to pay indemnity to customers that affected by outages throughout the year. In some cases the indemnity is more dominant part of EO cost for DCs whereas the unsold energy is another part of it. Indemnity motivates DCs to install energy storage units. Nevertheless energy storage systems have been applied to distribution substation, using for preventing EO was not well studied. Moreover, economic effects of energy storage system on distribution substation evaluated in. This work deals to prevent outages using energy storage units especially for customers experienced frequent EO. Different battery sizes and types selected according to supply whether whole outage duration or not. Results are examined for all cases.
Keywords: energy storage; power quality; cost analysis; distribution network; Automation & Control Systems; Computer Science; Engineering